L’activité géographique en France (Le maître Raoul Blanchard et le tome sixième de ses « Alpes occidentales ») - Pardé, Maurice (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
Geographical research and production in France have known a remarkable development during the last half century. One of the leaders of this contemporary movement bas been Professor Raoul Blanchard who was not only a chef d'école, but also a leader for his students and colleagues. Professor Blanchard has shown the way himself in publishing numerous important works on several parts of the world, and, of special interest to Canadians, his collection of regional monographs about French Canada. Not so well known to Canadian geographers and readers are his works (12 volumes) on the Alpes occidentales. In this article, a prominent French geographer, Professor Maurice Parde, of Grenoble, studies the influence of Professor Blanchard on the contemporary geographical movement in France. He also analyses more especially the sixth and last part of this monumental work on the Alps. Mr. Blanchard, who is an honorary president of the Canadian Association of Geographers, has recently been awarded a golden medal by the American Geographical Society.